Bitcoin Halving Cycles and Their Impact on the Gold Relationship - Mustaph KHALFOUNI; Rafia FRIJ; Mohammed Lamarti Sefian; Noaman LAKCHOUCH (Statistics, Optimization & Information Computing, 2025)
This paper examines the interdependencies between Bitcoin and gold within the context of Bitcoin halving cycles. Using a comprehensive econometric approach, including cointegration tests, VAR and VECM models, DCC-GARCH modeling, and wavelet coherence analysis, we investigate short- and long-term dynamics linking these two assets.Our findings indicate that, over the long term, Bitcoin exhibits characteristics similar to gold as a safe haven despite its high volatility and sensitivity to short-term shocks. Moreover, the incorporation of macroeconomic variables, such as stock market indices and oil prices, highlights the significant influence of broader economic conditions on this relationship. These results suggest that while Bitcoin may serve as a complementary asset to gold in diversified portfolios, prudent management is essential to mitigate the risks associated with its speculative nature.